Quality control of injectable artesunate marketed in Kisangani in the Democratic Republic of the Congo - Emile TWENI BARUTI; Jérémie Mbinze Kindenge; Jordan Mwanga Maombi; Luc Shabani Mitongo; Justin Kadima Ntokamunda; Roland Marini Djang'eing'a (Orapuh Journal)
Introduction